A Rare Metastatic Site of Invasive Lobular Breast Carcinoma: A Case Report - Sara Husain; Mohamed Isa; Raed Almarzooq (Case Reports in Surgery)
Here, we report a case of a 42-year-old female patient with left lobular breast cancer-gastric metastasis (initially misdiagnosed five years ago as an invasive ductal carcinoma) presenting with dyspepsia, weight loss, and persistent vomiting lasting for four weeks. Upper GI endoscopy revealed evidence of linitis plastica, and histological and immunocytochemical analyses of the biopsy confirmed gastric metastasis secondary to invasive lobular breast carcinoma.